The impact of gun control and gun ownership levels on violence rates - Kleck, Gary (Journal of quantitative criminology, 1993)
What effects do gun control restrictions and gun prevalence have on rates of violence and crime? Data were gathered for all 170 U.S. cities with a 1980 population of at least 100,000. The cities were coded for the presence of 19 major categories of firearms restriction, including both state- and city-level restrictions. Multiple indirect indicators of gun prevalence levels were measured and models of city violence rates were estimated using two-stage least-squares methods. The models covered all major categories of intentional violence and crime which frequently involve guns: homicide, suicide, fatal gun accidents, robbery, and aggravated assaults, as well as rape. Findings indicate that (1) gun prevalence levels generally have no net positive effect on total violence rates, (2) homicide, gun assault, and rape rates increase gun prevalence, (3) gun control restrictions have no net effect on gun prevalence levels, and (4) most gun control restrictions generally have no net effect on violence rates. There were, however, some possible exceptions to this last conclusion—of 108 assessments of effects of different gun laws on different types of violence, 7 indicated good support, and another 11 partial support, for the hypothesis of gun control efficacy.